Differences between english and the Zhuang language in phoneme and word stress - Zhien Liao; Kavitha Ganesan; Jane Wong Kon Ling (Academic Education Publishing, 2024)
The Zhuang language is the mother tongue of the Zhuang people that mainly live in Guangxi, China. It has two writing systems. One is called Sawndip based on Chinese characters. The other is called Standard Zhuang that is based on alphabets. Sawndip and Standard Zhuang share the same pronunciation, but they are completely different in form, and the later has been made as a teaching language in many primary and middle schools in Guangxi. Since the Reforming and Opening up in 1980s, English has become a compulsory course for Chinese students including Zhuang students. Although both Standard Zhuang and English share the same alphabet, they belong to different language families. Negative transfer of the mother tongue in learning English has been a challenge for the Zhuang students. Employing Contrastive Analysis, this paper analyzes the differences between Standard Zhuang and RP in phoneme and word stress. It may help English teachers to teach and Zhuang students to learn English better. It may also help the foreigners to better understand the Zhuang language and culture.